Evaluasi Penerapan GMP Menggunakan Diagram Fishbone di Industri Mie Instant PT. XYZ - Fahri Rizal Syahid; Aji Jumiono (Universitas Djuanda, 2025)
Good Manufacturing Practices (GMP) are guidelines in food production processes aimed at ensuring product safety, quality, and consistency. Evaluating GMP implementation is essential to identify non-conformance factors and develop corrective strategies. This study aims to evaluate GMP implementation in an instant noodle industry, PT. XYZ, using the fishbone diagram approach. The methodology involved in-depth interviews and observations as primary data sources, complemented by documentation studies and literature reviews as secondary data. The analysis revealed five main aspects influencing GMP effectiveness: man, method, machine, material, and environment. Contributing factors include inadequate training, weak monitoring systems, unhygienic machine design, non-standard raw materials, and suboptimal zoning and ventilation systems. The fishbone diagram effectively categorized root causes and served as a basis for designing corrective actions. Optimal GMP implementation is crucial for ensuring food safety, enhancing production efficiency, and maintaining the reputation of food industries in a competitive market.